Site-Specific Impact of a Regional Hydrodynamic Injection: Computed Tomography Study during Hydrodynamic Injection Targeting the Swine Liver - Takeshi Yokoo; Tsutomu Kanefuji; Takeshi Suda; Kenya Kamimura; Dexi Liu; Shuji Terai (MDPI AG, 2015)
A hemodynamic study of hydrodynamic gene delivery (HGD) from the tail vein in rodents has inspired a mechanism and an approach to further improve the efficacy of this procedure. However, there is no report on the hemodynamics of a regional HGD, which is an inevitable approach in large animals. Here, we report the hemodynamics of a regional hydrodynamic injection in detail based on 3D volume data and the dynamism of tissue intensity over time by using computed tomography (CT) both during and after a regional hydrodynamic injection that targeted the liver of a pig weighing 15.6 kg. Contrast medium (CM) was injected at a steady speed of 20 mL/s for 7.5 s under the temporal balloon occlusion of the hepatic vein (HV). A retrograde flow formed a wedge-shaped strong enhancement area downstream of the corresponding HV within 2.5 s, which was followed by drainage into another HV beginning from the target area and the portal vein (PV) toward a non-target area of the liver. After the injection, the CM was readily eliminated from the PV outside the target area. These data suggest that an interventional radiology approach is effective in limiting the hydrodynamic impacts in large animals at a target area and that the burden overflowing into the PV is limited. A further investigation that simultaneously evaluates gene delivery efficiency and hemodynamics using CT is needed to establish feasible parameters for a regional HGD in large animals.